(untitled) (REMUNOM, 2024)
Candidiasis is an opportunistic fungal infection caused by microorganisms of the Candida genus, the most common in the oral cavity. Candida fungi are present in the healthy oral microbiota, however the conditions in which they are inserted can favor their growth, making them pathogenic. There is a vast market for antifungal drugs that are used to treat candidiasis, among them, azole antifungals (ketoconazole, fluconazole) and polyene antifungals (nystatin, amphotericin B). However, several challenges have been observed regarding the efficacy of drug treatment, such as resistance of fungal strains to antifungals, patient adherence, indiscriminate use and adverse effects of synthetic drugs. Thus, the use of medicinal plants has proven to be a promising and favorable alternative for the discovery of new phytopharmaceutical agents with great biological potential. Based on studies in the literature that demonstrate the physicochemical and ethnopharmacological characteristics of medicinal plant species, this research aims to evaluate the antifungal activity of the acetate extract of Psidium guineense (Myrtaceae). The study was carried out through in vitro assays where the ethyl acetate extract of Psidium guineense was used as a test substance against the fungal species of Candida glabrata and Candida parapsilosis previously identified and maintained in Sabouraud dextrose agar culture media - ASD. Furthermore, nystatin was used as a standard antifungal agent to perform the positive control. Therefore, the broth microdilution technique was performed to determine the minimum inhibitory concentration (MIC) of the ethyl acetate extract of Psidium guineense. After reading the MIC in 24 hours, all analyses and tests were performed in duplicate. Therefore, with the execution of this unprecedented research, it was observed that the ethyl acetate extract presented a MIC greater than 1024 μg/mL-1 for all tested strains of Candida glabrata and Candida parapsilosis, that is, it did not present antifungal activity. Thus, it is worth highlighting the need for new research, using other strains of fungus to verify the antimicrobial potential of the compound in question. Thus, more research is needed, including changing its methodologies so that new products of plant origin can be found, with effective antifungal activity so that it can be implemented among health technologies, to combat fungal infections and mitigate the exponential increase in fungal resistance that becomes an obstacle to achieving the success of drug treatment applied to Dentistry. Keywords: Pharmacology; Phytotherapy; Dentistry.